KINEMATICS ANALYSIS OF MECHANISMS AS A PART OF TECHNICAL MECHANICS EDUCATION - MONKOVÁ, Katarína; MONKA, Peter; ŠMERINGAIOVÁ, Anna; KASINA, Marek (Trends in education, 2011)
The article deals with kinematics analysis of mechanism at the Technical mechanics education at FMT TU Košice with seat in Prešov. The virtual environment with 3D models is the supporting medium at the specific problem teaching. The article shows on the possibility of CAD/CAM system utilization within the subjects, which are not direct connected with 3D modelling. Students acquaint with 3D version of mechanism not only in static position, but also in so called "active status", they understand how the individual components work and consequently they come up to the problem solution. This article originates with the direct support of Ministry of Education of Slovak republic by grants VEGA num. 1/0885/10 and KEGA num. 270-014TUKE-4/2010.
Keywords: mechanism; kinematics analysis; virtual model.